Efek Protektif Madu Terhadap Ginjal Tikus Putih Yang Diinduksi Etanol - - Muhartono; Rizki Hanriko; Haryani Dwita (Fakultas Kedokteran Universitas Lampung, 2012)
Honey already used as natural food sources since long time ago. Honey has been shown contained active chemical compounds that are antioxidants, yet there is still only a few experimental studies about the protective effect of honey against ethanol-induced renal damage. This study aims to prove the protective effect of honey against renal damage and determine the relationship of increasing doses of honey against renal damage in male rat (Rattus norvegicus). Research subjects were used 25 Sprageu dawley strain male rat. Rat weredivided into 5 groups that was negative control were given only distilled, positif control (only given ethanol 0,01 ml/gBW/day), treatment group I (given honey 0,0018 ml/gBW/day dan ethanol 0,01 ml/gBW/day), treatment group II (given honey 0,0054 ml/gBW/day dan ethanol 0,01 ml/gBW/day), treatment group III (given honey 0,0162 ml/gBW/day dan ethanol 0,01 ml/gBW/day) for 14 days. Based on result of the Kruskal wallis test performed on this data p<0,05, which mean there were protective effect of giving the honey treatment to renal damage male rat. Mann whitney test result p <0,05, which means that there were significant differences proximal tubulus on rat almost found between each groups except positif control group with treatment group I and treatment group II with treatment group III. Honey shown to have protective effects against ethanol-induced renal damage of Sprageu dawley strain male rat. Increasing doses of honey can increase the protective effects against the renal damage of Sprageu dawley strain male rat at certain dose, on dose 0,0018 ml/gBW/day and 0,0054 ml/gBW/day